Privacy-Preserving Online Content Moderation: A Federated Learning Use Case - Leonidou, Pantelitsa; Kourtellis, Nicolas; Salamanos, Nikos; Sirivianos, Michael (My University, 2023)
Users are exposed to a large volume of harmful content that appears daily on various social network platforms. One solution to users' protection is developing online moderation tools using Machine Learning (ML) techniques for automatic detection or content filtering. On the other hand, the processing of user data requires compliance with privacy policies. In this paper, we propose a framework for developing content moderation tools in a privacy-preserving manner where sensitive information stays on the users' device. For this purpose, we apply Differentially Private Federated Learning (DP-FL), where the training of ML models is performed locally on the users' devices, and only the model updates are shared with a central entity. To demonstrate the utility of our approach, we simulate harmful text classification on Twitter data in a distributed FL fashion- but the overall concept can be generalized to other types of misbehavior, data, and platforms. We show that the performance of the proposed FL framework can be close to the centralized approach - for both the DP-FL and non-DP FL. Moreover, it has a high performance even if a small number of clients (each with a small number of tweets) are available for the FL training. When reducing the number of clients (from fifty to ten) or the tweets per client (from 1K to 100), the classifier can still achieve AUC. Furthermore, we extend the evaluation to four other Twitter datasets that capture different types of user misbehavior and still obtain a promising performance (61% - 80% AUC). Finally, we explore the overhead on the users' devices during the FL training phase and show that the local training does not introduce excessive CPU utilization and memory consumption overhead.
Keywords: Content moderation; Federated learning; Privacy